Assessment of adverse oral habits and awareness of tobacco as risk factor for oral cancer among unskilled workers in Yenepoya University, Mangalore - Nagaratna B Bagewadi; Ganesh Shenoy Panchamal; Rekha Shenoy; Praveen Jodalli (Journal of Indian Association of Public Health Dentistry, 2013)
Background: It is estimated that in India one million deaths occur due to tobacco every year. If left unchecked, it is projected that the mortality due to tobacco consumption will rise to 1.5 million by 2020. Objectives: To assess the knowledge, awareness, chewing practices and adverse effects of tobacco as risk factor for oral cancer among unskilled workers in Yenepoya University. Materials & Method: A cross sectional study was conducted among the unskilled workers in Yenepoya University. A pretested self administered questionnaire was used to record the response regarding knowledge, awareness and adverse effects of tobacco chewing practices among the subjects. The data collected were tabulated and subjected to statistical analysis, Cronbach a was used to assess internal consistency. Results: The study population consisted of 280 unskilled workers in Yenepoya University. Among them 169(60.4%) consumed tobacco; 155(91.7%) people consuming tobacco were aware of the harmful effects of tobacco consumption and 14(8.3%) were unaware; 162(95.3%) workers were aware of oral cancer and 7(4.7%) workers didnothave knowledge about oral cancer. Conclusions: Even though the study population were aware of harmful effects of tobacco and oral cancer, the prevalence of tobacco usage was found to be high.